Mineralogy, petrology and geohemistry of amphibolites from the Kalnik Mt. (Sava Unit, North Croatia): implications for the evolution of north-westernmost part of the Dinaric-Vardar branch of Mesozoic Tethys - Šegvić, Branimir; Lugovíć, Boško; Meyer, Hans-Peter (Ofioliti, 2016)
This paper brings a first comprehensive set of mineralogical, petrological and geochemical data of amphibolites associated with mantle peridotites in the Upper Jurassic to mid Lower Cretaceous ophiolite mélange of Kalnik Mt. in northern Croatia. This mélange is emplaced in a Paleogene sedimentary succession. Metamorphic evolution of the amphibolites and the nature of their igneous protoliths are discussed in the frame of late history development of north-western branch of Dinaric-Vardar Tethys. Primary amphibolite assemblages consist of pargasite-magnesio-hornblende and oligoclase-bytownite (common amphibolite) + almandine-grossular-rich garnet (garnet amphibolites) + clinopyroxene (clinopyroxene amphibolites). Minimum equilibration temperature for the amphibole-plagioclase pairs was estimated at 660±40°C, whereas the peak conditions (790±20°C at 0.79 to 1.04 Gpa) were recorded in garnet amphibolite. Retrograde parageneses (albite, actinolite, clinozoisite, titanite, chlorite, pumpellyite, and ‘metamorphic vermiculite’) correspond to greenschist to sub-greenschist facies conditions. Protolith REE patterns match modern ocean ridge basalts (LaN/LuN = 0.51-0.82) whilst the normalized multi-element diagram shows slight negative HFSE anomalies (NbN/LaN = 0.44-0.90), diagnostic for a subduction-zone geochemical signature. Overall, geochemical data suggest back-arc basin (BAB) tholeiitic mafic extrusives (lack of Eu anomaly) and IAT-like cumulates (Eu positive anomaly) as amphibolite precursors. We propose that the protoliths of the Kalnik Mt. amphibolites represented a metamorphic sole formed at the expense of an oceanic crust originated at the ridge of a back-arc marginal basin. The metamorphism must have taken place during Tithonian (?) as inferred from the protolith age. According to the geological evidences the back-arc magmatic regime was active until the final closure of Mesozoic Tethys in Cretaceous by the obduction of Dinaric ophiolites onto the NW margins of Adria microplate, when part of the metamorphic sole must have been exhumed and obducted together with the rest of ophiolite sequence.